The Implementation of Accounting Objectives: An Application to Extraordinary Items. - Barnea, A.; Ronen, J.; Sadan, S. (The Accounting Review, 1975)
Presents a study which examined the implications of the report on accounting objectives (AICPA, 1973, called Report) to the reporting of extraordinary items. Trade-off between reliability and relevance; Framework for getting standards for the treatment of extraordinary items that are responsive to the accounting objectives as stated in the AICPA Study Group Report; Systematic path of inquiry that may be followed in the formulation of future accounting standards.